The Influence of Maternal Nutrition and Micronutrient Intake on the Incidence of Low Birth Weight (LBW) - Eka Sarofah Ningsih; Khusnul Nikmah; Ida Susila (Jurnal Penelitian Pendidikan IPA, 2025)
Low Birth Weight (LBW) is an important indicator in assessing the health status of newborns, and contributes to increased neonatal morbidity and mortality rates. Maternal factors, especially nutritional status and adequacy of micronutrient intake during pregnancy, are known to influence the incidence of LBW. This study aims to determine the relationship between maternal nutritional status and micronutrient intake (iron and folic acid) with the incidence of LBW in the Deket Health Center working area, Lamongan Regency. This study used a descriptive analytical design with a cross-sectional approach. The population consisted of 11 pregnant women who gave birth at the Deket Health Center in 2024. Data were collected through structured interviews, nutritional status assessments based on KEK indicators, and assessments of iron and folic acid intake. The analysis was carried out using the Fisher's Exact Test. Of the 11 respondents, 3 cases of LBW were found. There were 3 mothers who experienced KEK, 6 mothers with insufficient iron intake, and 7 mothers who did not meet folic acid needs. The results of statistical tests showed that the relationship between nutritional status and micronutrient intake with the incidence of LBW was not statistically significant (p = 0.091), but showed a tendency for a clinically relevant relationship. Nutritional status and adequacy of micronutrient intake of pregnant women have the potential to influence the incidence of LBW although the relationship was not statistically significant. Prevention efforts through nutritional education and monitoring the status of pregnant women need to be strengthened as part of health services at the Community Health Center.